ANALISIS KETERAMPILAN GURU SEJARAH DALAM MENGADAKAN VARIASI PEMBELAJARAN DI SMAN 10 PONTIANAK - Beny Rusdy; Junaidi H Matsum; Ika Rahmatika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract The aims in this research is to know skills of history teacher in learning variation practice on SMAN 10 Pontianak. The method in this research was descriptive. The form of research was case studies. A source of data in this research was history teacher,representatives of students, and school principals in SMAN 10 Pontianak. The collecting of data on this research used observation, interview, and documenter. The analysis in this research was apply interactive model which the stages data reduction, data display, and conlusion drawing. The result of this research is (1) Teaching style variation have been very good. (2) Teaching the pattern of interaction variation still dissatisfactory because unsuitable with learning variation aspects. (3) Teacher applying the tools learning variation of second teachers is still not maximum using visual media. The conlusion is learning variation that applying still dissatisfactory so that there are some aspects not use in history learning Keywords: History Learning, Learning Variation, Teacher